Nestanak Tomislava Matanovića / The Disappearance of Tomislav Matanović: Postupak pred Domom za ljudska prava / The Human Rights Chamber Case - Karčić, Hikmet (Pregled: časopis za društvena pitanja / Periodical for social issues, 2016)
The aim of this paper is to deal with one of the most interesting cases in front of the Human Rights Chamber in Bosnia and Herzegovina. The disappearance of Vojislav Matanović and his parents sparked a lot of attention of international subjects and the Catholic Church. Twenty years after their disappearance, their fate is still not clear.